Smart greenhouse fuzzy logic based control system enhanced with wireless data monitoring. (March 2016) - Azaza, M.; Tanougast, C.; Fabrizio, E.; Mami, A.
Abstract: Greenhouse climate control is complicated procedure since the number of variables involved on it and which are dependent on each other. This paper presents a contribution to integrate greenhouse inside climate key׳s parameters, leading to promote a comfortable micro-climate for the plants growth while saving energy and water resources. A smart fuzzy logic based control system was introduced and improved through specific measure to the temperature and humidity correlation. As well, the system control was enhanced with wireless data monitoring platform for data routing and logging, which provides real time data access. The proposed control system was experimentally validated. The efficiency of the system was evaluated showing important energy and water saving. Highlights: Smart control to manage an agriculture production system. FLC system which integrates all greenhouse inside climate keys parameters. Improved FLC through specific measure to the temperature and humidity correlation. The system control was enhanced with wireless data monitoring platform. The efficiency was evaluated showing important energy and water saving.